Determinant Factors of Firm Value in Coal Mining Firms: Evidence from Indonesia - Cahyono, Koko; Nursanita, Nursanita (Santoso Academy Network, 2024)
This research investigates how firm value in coal mining companies is influenced by profitability, leverage, and corporate governance between 2014 and 2020. Utilizing a quantitative approach with a descriptive methodology, the study analyzed secondary data from 21 coal companies, totaling 147 data points, sourced from the Indonesian Stock Exchange (BEI). Findings reveal that Debt-to-Equity Ratio (DER) and the presence of an Independent Board of Commissioners positively affect firm value. Conversely, managerial ownership and the Audit Committee's impact on firm value were negligible, due to limited managerial stakes and inadequate audit committees. Return On Assets (ROA) did not affect firm value, likely due to significant data variation and decreasing trends. The study suggests that a robust corporate governance structure ensures informed decision-making and minimizes strategic errors. Management should focus on enhancing operational efficiency to boost profitability.